2022
DOI: 10.3390/ijerph192013002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Teaching Mini Handball through Non-Linear Pedagogy in Different Socioeconomic Contexts: A Pilot Study

Abstract: Mini handball is among the sports included as part of school physical education in Chile to improve children’s motor skills and to motivate their adherence to a healthy and active lifestyle in response to concerns about this country’s high level of childhood obesity. To this end, non-linear pedagogy (NLP) has been used to develop motor skills through mini handball in the school context. However, socioeconomic differences that influence the development of children’s motor skills have not been considered to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In this regard, previous studies have conducted different protocols that may be helpful for improving IR ROM in overhead throwing athletes [ 42 , 43 ]. In addition, previous studies also showed that self-regulated training and non-linear pedagogy in handball can improve running speed and jump height as well as motor skill [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies have conducted different protocols that may be helpful for improving IR ROM in overhead throwing athletes [ 42 , 43 ]. In addition, previous studies also showed that self-regulated training and non-linear pedagogy in handball can improve running speed and jump height as well as motor skill [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%